Teaching development programs as activators of the reflective practice of learning processes: integrative review - Kuczner Pereira, Felipe (2021)
The reflection of the practice of learning processes, through participation in teacher development programs, contributes to professional emancipation and to the consolidation of an autonomous profession. It aimed to analyze the scientific evidence on the use of teacher development programs to activate the reflective practice of learning processes. It is an integrative review carried out in the SciELO, DOAJ and ERIC databases, in the period 2016-2020, resulting in 17 studies related to the theme. 9 (53%) publications redeemed on the DOAJ database were eligible, 6 (35%) on ERIC and 2 (12%) on SciELO. Studies have shown that continuing education programs are options to assist teachers in the process of reflecting on practice.